Unveiling the silent nemesis: periprosthetic joint infection-the burden and road to recovery - Ganesh, Arjun; Kumar, M. Mohan (International Journal of Research in Orthopaedics, 2023)
Periprosthetic joint infection (PJI) is a devastating complication of joint replacement surgery that poses significant challenges for patients and healthcare systems. It is associated with increased morbidity, financial burdens, and emotional distress for patients. Understanding the risk factors for PJI and implementing preventive strategies are crucial to reducing its incidence and mitigating its impact on both individuals and healthcare institutions.